Incidence of Corrected QT Prolongation With Concomitant Methadone and Atypical Antipsychotics in Critically Ill Children - Hughes, Kaitlin M. (J Pediatr Pharmacol Ther, 2021)
OBJECTIVE: To evaluate the safety of the combination of methadone and an atypical antipsychotic in PICU patients. METHODS: This was a retrospective observational cohort pilot study in a single-center PICU in an academic children's hospital. Children 1 month to 18 years of age were included if they received methadone, were then initiated on an atypical antipsychotic (i.e., quetiapine or risperidone), and had EKG monitoring before and after medication initiation. RESULTS: Prolongation of the corrected QT (QTc) interval occurred in 5 of the 34 included patients when an atypical antipsychotic was added to methadone. Of the 5 patients who had a prolonged QTc interval, 4 (80%) were older than 12 years and had a median weight of 91.3 kg. There were statistical differences between age and weight when comparing patients who experienced QTc prolongation, but no differences in sex, ethnicity, electrolyte deficiencies, number of additional QTc-prolonging medications, and number of additional drug-drug interactions were identified. When comparing atypical antipsychotics, 9.5% of patients receiving risperidone had a prolonged QTc interval, versus 23% of patients receiving quetiapine (p = 0.04). The net change in QTc interval after initiation of methadone was 0.19 milliseconds (IQR: −3, 15), which increased after atypical antipsychotic initiation to 4 milliseconds (IQR: −16, 15). CONCLUSIONS: Our pilot trial suggests there is no clinically significant difference in incidence of QTc prolongation with addition of atypical antipsychotics to methadone.